Abiotic and Biotic Stress in Plants - Recent Advances and Future Perspectives 2016
DOI: 10.5772/61957
|View full text |Cite
|
Sign up to set email alerts
|

Role of ABA in Arabidopsis Salt, Drought, and Desiccation Tolerance

Abstract: The ability of plants to respond to environmental stimuli is essential to plant survival. Abscisic acid ABA is a phytohormone with roles at various stages of plant development. ABA also plays a major role in mediating physiological responses to environmental stresses such as salt, osmotic, and cold stress. Plant responses to environmental stress have been widely studied in the model plant Arabidopsis thaliana and ABA signaling mechanisms elucidated. In general, the adaptive responses of plants to various stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 75 publications
1
40
0
1
Order By: Relevance
“…Treatment with ABA resulted in nearly complete silencing of the antisense promoter activity in leaves, compared to mock‐ or GA‐treated plants (Figs A and B, and EV2A and B, Appendix Fig S1). ABA plays an important role in the response of plants to stress, including water deprivation where it acts as part of a signalling cascade leading to drought resistance . Subsequently, we showed that the DOG1 antisense promoter was also strongly downregulated in response to 5 days of water withdrawal (Figs C and D, and EV3A–C), a result validated by strand‐specific RT–qPCR analysis in Col‐0 (WT) plants (Fig E).…”
Section: Resultssupporting
confidence: 66%
“…Treatment with ABA resulted in nearly complete silencing of the antisense promoter activity in leaves, compared to mock‐ or GA‐treated plants (Figs A and B, and EV2A and B, Appendix Fig S1). ABA plays an important role in the response of plants to stress, including water deprivation where it acts as part of a signalling cascade leading to drought resistance . Subsequently, we showed that the DOG1 antisense promoter was also strongly downregulated in response to 5 days of water withdrawal (Figs C and D, and EV3A–C), a result validated by strand‐specific RT–qPCR analysis in Col‐0 (WT) plants (Fig E).…”
Section: Resultssupporting
confidence: 66%
“…Although closing the stomata could be an immediate adaptive response for protection against salt shock by reducing water loss, soybean seedlings also need to at least partially resume transpiration and photosynthesis by reopening them. ABA is a major regulator of stomatal closure, and the ABA signaling pathway is well known to be associated with responses to environmental stresses (Fernando & Schroeder, ). Here, we observed the induction of genes for ABA biosynthesis and ABF, a major downstream TF, as well as other ABA response genes such as RD29B and RD22 (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signal transduction pathways are activated to cope with salt stress, such as the phytohormone‐mediated, Ca 2+ ‐dependent, and phosphatidylinositol signals (Fernando & Schroeder, ; Ji et al, ; Xue, Chen, & Mei, ). These signaling pathways activate other regulators, such as transcription factors (TFs) to amplify the signals for gene regulation, and finally initiate protective mechanisms through the induction or repression of functional genes (Lata, Yadav, & Prasad, ).…”
Section: Introductionmentioning
confidence: 99%
“…High salinity and high osmolality induce an increase of endogenous ABA levels (Fernando & Schroeder, ) and PGG arrest. We examined whether AtRaf22 modulates the arrest of PGG induced by high salinity or osmolality.…”
Section: Resultsmentioning
confidence: 99%